Network tool for preventing DDOS attacks on cloud computing - Yo, Kee Seng (Universiti Malaysia Sarawak (UNIMAS), 2015)
Securing a cloud computing environment has been a major development in computer network. Cloud computing services are popular for its ease of use and dynamic scalability with great reliability feature. Wireless broadband network offers dynamic feature in cloud computing services. Despite the fact that wireless broadband network in susceptible to security attacks, it is still widely used in modern days. With the right security protocol implementation, securing cloud computing environment will allow cloud computing to provide a better service and performance. This algorithm is simple and it is based on existing security protocol and is proposed for detecting and preventing security attacks on the network by filtering packets in the network. The algorithm is implemented in a simulated network environment and results obtained is analyze based on packet delivery ratio.